Ekosysteemitoiminnan keskeiset elementit - Kuosmanen, Tero (2024)
Over the past decade, ecosystems have garnered increasing interest among management researchers, as part of a broader shift toward systemic and net-worked thinking. Ecosystems allow the examination of business and innova-tion processes within a broader, networked context, offering a novel perspec-tive on traditional management and strategy theories. Ecosystem research draws from various fields, such as innovation, entrepreneurship, and strategy studies, making it an interdisciplinary research area. This diversity brings challenges in creating a common terminology and conceptual framework. Platforms play a central role in ecosystems, facilitating interaction among ac-tors and enabling innovation and product development. Platforms serve as a foundation for building ecosystems where actors benefit from mutual interac-tion and collaboration. Networks, on the other hand, are based on reciprocal relationships and resource sharing to achieve common goals. Ecosystems can be understood as complex networks where value propositions and operation-al elements vary depending on the context. Despite extensive research, a uni-fied definition of ecosystems is still lacking. The purpose of this thesis is to analyze the key elements of a successful ecosystem and produce an artifact model for the LTH ecosystem. The results emphasize the critical role of the ecosystem leader and highlight the importance of collaboration, trust, and openness for ecosystem success. The artifact provides a clear framework for ecosystem design and development.